The wakame gatherers - Thompson, Holly (Shen's Books, 2007)
When Nanami's Gram from Maine visits Japan, Nanami's Japanese grandmother, Baachan, takes them to the seashore to gather wakame seaweed. Includes several recipes for wakame.